131I-labeled multifunctional dendrimers modified with BmK CT for targeted SPECT imaging and radiotherapy of gliomas. (May 2016) - Cheng, Yongjun; Zhu, Jingyi; Zhao, Lingzhou; Xiong, Zhijuan; Tang, Yueqin; Liu, Changcun; Guo, Lilei; Qiao, Wenli; Shi, Xiangyang; Zhao, Jinhua
Aim: The poly(amidoamine) dendrimers modified with Buthus martensii Karsch chlorotoxin (BmK CT) were developed as a 131 I delivery system for glioma-targeted imaging and therapy.Materials & methods: Dendrimers before and after labeling 131 I were synthetized and their physicochemical properties were tested. The targeting and therapeutic efficacy of 131 I-G5.NHAc-HPAO-(PEG-BmK CT)-(mPEG) dendrimer against glioma was evaluated in vitro and in vivo .Results: All the dendrimers were stable under different conditions. BmK CT modification increased the cellular uptake of dendrimers in C6 glioma cells, but not in the normal RLE-6TN cells. 131 I-G5.NHAc-HPAO-(PEG-BmK CT)-(mPEG) dendrimer was radiochemically pure and could be applied in glioma-targeting single-photon emission CT (SPECT) imaging and radiotherapy.Conclusion: 131 I-G5.NHAc-HPAO-(PEG-BmK CT)-(mPEG) complex is a promising multifunctional nanoplatform for glioma-specific nuclear imaging and radiotherapy.